Efektivitas Pupuk Hayati terhadap Pertumbuhan dan Hasil Jagung Hibrida di Tanah Alfisol - Supriyono, Supriyono; Nurmalasari, Aprilia Ike; Sulistyo, Trijono Djoko; Fatimah, Siti (Agrotechnology Research Journal, 2022)
The use of biological fertilizers on maize is one way to increase crop productivity which refers to sustainable agriculture. This study aims to determine the effect of biological fertilizers on the growth and yield of hybrid maize. The research was conducted from May to September 2019 at the Jumantono Experimental Garden in Sukosari village, Jumantono, Karanganyar. The method used was a factorial Randomized Complete Block Design (RCBD) with one factor, namely the dose of biological fertilizer consisting of 4 levels, 0, 12, 20, and 28 L.ha-1), Liquid biological fertilizers used are biological fertilizers containing Azospirillum sp., Azotobacter sp., and Bacillus sp. The results showed that the 12 L.ha-1 dose of biofertilizer significantly affected plant height, stem diameter, and leaf area index compared to the control (0 L.ha-1). Biofertilizer was able to increase plant height, stem diameter, and leaf area index by 9.3, 13, and 19%, respectively. The optimum dose of biofertilizer on acid soils was 12 L.ha-1 with a seed yield of 3.5 tons.ha-1 or an increase of 23.02% compared to control. This study concludes that the dose of 12 L.ha-1 can be used as a recommendation to farmers for hybrid maize cultivation on acid land.